An illustrated catalog of the South American Austroleptidae (Diptera: Tabanomorpha), with a compilation of all known records and new records from Chile and Argentina - Fachin, Diego Aguilar; González, Christian R.; Elgueta, Mario; Hauser, Martin (Zootaxa, 2024)
A list of all eight species of Austroleptis Hardy, 1920, the only genus of Austroleptidae, from South America is provided, including photos of type specimens of four Chilean species and all distributional records given in the literature and from labels of newly examined material, which are added into a map. The list of species, including photos of additional material, is presented in a catalog format that gives all nomenclatural information and relevant literature about the species. Two undescribed species are indicated and four described species have their distribution expanded: A. atriceps Malloch, 1932 is now recorded in La Araucanía Region, Chile, and in Río Negro Province, Argentina; A. breviflagella Nagatomi & Nagatomi, 1987 has its first records for Ñuble and La Araucanía Regions; A. fulviceps Malloch, 1932 is now reported from Maule and Ñuble Regions; and A. penai Nagatomi & Nagatomi, 1987 is now reported from Los Lagos Region.